Implementation of Prudential Principle in Sharia Digital Banking Financing for Risk Mitigation - Putri Sari Arafah Hasibuan; Tri Inda Fadhilla Rahma; Fauzi Arif Lubis (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study analyzes the implementation of the prudential principle in Islamic banking financing within the digital era as a strategic instrument for risk mitigation. The rapid digital transformation in Islamic banking has shifted financing processes from conventional mechanisms toward technology-driven systems, including digital onboarding, electronic identity verification, big data analytics, and automated risk assessment. While digitalization enhances efficiency and financial inclusion, it simultaneously introduces new risks such as cybersecurity threats, data manipulation, operational failures, and Sharia compliance challenges. Employing a descriptive qualitative approach, this research integrates empirical insights, juridical-normative analysis, and bibliometric mapping. Primary data were obtained through interviews with Islamic banking practitioners engaged in digital financing and risk management, while secondary data were drawn from regulations, academic literature, and industry reports. Bibliometric analysis using VOSviewer identified dominant themes and research gaps related to prudential principles, Islamic banking, and digital risk governance. Findings reveal that the prudential principle has evolved into a multidimensional governance system encompassing financing analysis, technology validation, cybersecurity, data protection, operational supervision, and Sharia compliance. The study concludes that digital transformation reinforces rather than diminishes the relevance of prudential principles, contributing to theoretical discourse on Islamic digital finance and offering practical recommendations to strengthen risk management, financial stability, and public trust.